Creative Writing Training to Enhance Creative Ideas and Imagination in Short Story Writing for PKK in Bakalan Village, Pasuruan City - Mardiningsih (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Writing short stories is an effective way to express creative ideas, experiences, and imagination. The Women's Group (PKK) plays a very strategic role in empowering women and improving the quality of family life. One way to strengthen this role is by developing literacy skills, such as writing short stories. This creative writing training in short story writing aims to 1) enhance the writing skills and creativity of the PKK women in Kelurahan Bakalan, 2) provide basic knowledge about the techniques and structure of short story writing, 3) build the confidence of the women in writing and expressing themselves through short stories, and 4) encourage the PKK women of Kelurahan Bakalan to publish their short stories in print or online media to be commercialized, thereby creating economic opportunities that can improve family welfare. The method used in this community service activity for creative writing training in short story writing is a structured, participatory training method with intensive guidance to ensure participants can follow, understand the material, and write short stories effectively. The target group for this community service in creative writing training in short story writing is the PKK women of Kelurahan Bakalan, Pasuruan City, totaling 25 (Kelurahan Bakalan PKK administrators). The training instruments include participant worksheets as a reference for writing short stories and an assessment rubric to evaluate the short stories written by the PKK women of Kelurahan Bakalan, Pasuruan City. The results of this creative writing training in short story writing showed good outcomes with the following details: 1) an improvement in short story writing skills among the PKK women of Kelurahan Bakalan, indicated by the high scores of the short stories based on the assessment rubric applied in the training, 2) increased self-confidence as indicated by the willingness of the PKK women of Kelurahan Bakalan to present their written works in public, 3) enthusiasm and commitment of the participants as indicated by their commitment to continue creating short stories, which will be published in an anthology, a collection of short stories written by the PKK women of Kelurahan Bakalan, Pasuruan City.